Tropism of Newcastle disease virus strains for chicken neurons, astrocytes, oligodendrocytes, and microglia - Butt, Salman L. (BMC Vet Res, 2019)
BACKGROUND: Newcastle disease (ND), which is caused by infections of poultry species with virulent strains of Avian orthoavulavirus-1, also known as avian paramyxovirus 1 (APMV-1), and formerly known as Newcastle disease virus (NDV), may cause neurological signs and encephalitis. Neurological signs are often the only clinical signs observed in birds infected with neurotropic strains of NDV. Experimental infections have shown that the replication of virulent NDV (vNDV) strains is in the brain parenchyma and is possibly confined to neurons and ependymal cells. However, little information is available on the ability of vNDV strains to infect subset of glial cells (astrocytes, oligodendrocytes, and microglia). The objective of this study was to evaluate the ability of NDV strains of different levels of virulence to infect a subset of glial cells both in vitro and in vivo. Thus, neurons, astrocytes and oligodendrocytes from the brains of day-old White Leghorn chickens were harvested, cultured, and infected with both non-virulent (LaSota) and virulent, neurotropic (TxGB) NDV strains. To confirm these findings in vivo, the tropism of three vNDV strains with varying pathotypes (SA60 [viscerotropic], TxGB [neurotropic], and Tx450 [mesogenic]) was assessed in archived formalin-fixed material from day-old chicks inoculated intracerebrally. RESULTS: Double immunofluorescence for NDV nucleoprotein and cellular markers showed that both strains infected at least 20% of each of the cell types (neurons, astrocytes, and oligodendrocytes). At 24 h post-inoculation, TxGB replicated significantly more than LaSota. Double immunofluorescence (DIFA) with markers for neurons, astrocytes, microglia, and NDV nucleoprotein detected the three strains in all three cell types at similar levels. CONCLUSION: These data indicate that similar to other paramyxoviruses, neurons and glial cells (astrocytes, oligodendrocytes, and microglia) are susceptible to vNDV infection, and suggest that factors other than cellular tropism are likely the major determinant of the neurotropic phenotype. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12917-019-2053-z) contains supplementary material, which is available to authorized users.